Kebijakan Utang Berpengaruh Positif dan Signifikan terhadap Nilai Perusahaan: Bukti Empiris dari Perusahaan Manufaktur Sektor Barang Konsumen Primer - Olivia, Melisa; Iryanto, M. Budi Widiyo (Global Research on Economy, Business, Communication, and Information, 2024)
The company's main goal is to achieve maximum profits by utilizing the resources it has and maximizing company value. This research aims to analyze the influence of debt policy on company value which is moderated by business risk. This research is motivated by the inconsistency of previous findings regarding the relationship between debt policy and company value, and not many studies have paid attention to business risk factors in the context of debt policy decision making. This research is based on three main theories, namely the Modigliani-Miller Theory, Trade-Off Theory, and Pecking Order Theory. This research uses quantitative methods with data collection techniques through observations of the annual financial reports of companies in the primary consumer goods sector during the 2020-2022 period. Data analysis techniques for testing variables and hypotheses were carried out using WarpPLS Version 7.0 software. This research produces findings that debt policy has a positive and significant effect on company value and business risk moderates the relationship between debt policy and company value.